ESTIMATING FUTURE TRENDS OF HIV PREVALENCE AMONG INDIVIDUALS AGED 15-49 YEARS IN TANZANIA USING HOLT’S LINEAR METHOD - Dr. Smartson. P. NYONI; Thabani NYONI (European Science Publishing, 2024)
This study uses annual time series data of HIV prevalence among individuals aged 15-49 years for Tanzania from 1990 to 2020 to predict future trends of HIV prevalence over the period 2021 to 2030. The study utilizes Holt’s linear exponential smoothing model. The optimal values of smoothing constants α and β are 0.9 and 0.1 respectively based on minimum MSE. The results of the study indicate that annual HIV prevalence among individuals aged 15-49 years will continue to decline over the out of sample period. Therefore, there is need to continuously support HIV case detection, prevention and treatment especially among high-risk groups.
Keywords: Exponential smoothing, Forecasting, HIV prevalence